Description of the larva of Argia chelata Calvert, 1902 (Odonata: Coenagrionidae) - Novelo-Gutiérrez, Rodolfo (Zootaxa, 2013)
The larva of Argia chelata is described and figured. It falls into the group of Argia larvae with a moderately prominent ligula and two palpal seta, but it differs from its closest relatives by having labial palp with 2 setae plus one basal setella; the length of the ligula is 30% of its maximum width; basal tergites (1–5) lacking long, fine setae, mainly on midline; S8–10 mostly dark brown; paraprocts with spiniform setae on basal 0.25 and 0.55 of dorsal and ventral borders, respectively. Larvae were found in 2nd to 4th order shallow streams in cloud forest, crawling among debris, fine sand and mud where the water flow is slow or still, close to the shoreline. The larva is compared with A. lacrimans (Hagen), A. pima Garrison, and A. tonto Calvert, species apparently closely related.